The Signs That Bind: Why Tamar Requested Judah's Signet, Cor, and Staff - ʿAmar, Zohar (The Biblical archaeology review, 2021)
One of the more dramatic stories in the Bible appears in Genesis 38. It tells of the relationship between the patriarch Judah and his widowed daughter-in-law Tamar. Following the death of her husband, and after her hopes of being redeemed from widowhood by levirate marriage are disappointed by none other than Judah himself, Tamar […]